A Numerical and Experimental Simulation Study of the Fluid Flow Characteristics of the Past Horizontal Stabilizer and Elevator of the Microlight Aircraft Model - Salam, Nasaruddin; Tarakka, Rustan; Kasim, Lukman (Engineering, Technology & Applied Science Research, 2025)
A microlight aircraft named PPH-Unhas was developed at Hasanuddin University in Makassar, Indonesia, in 2020. This study aims to produce the characteristics of the lift coefficient (CL), drag coefficient (CD), and flow simulation on the horizontal stabilizer and elevator model of the PPH-Unhas microlight aircraft. Numerical simulations were conducted using a Computational Fluid Dynamics (CFD) program, and experiments were performed in a low-speed wind tunnel. The microlight aircraft model was made of three pieces adapted to the PPH-Unhas aircraft prototype and then tested by treating five levels of airflow velocity (V): 14, 16, 18, 20, and 22 m/s. Each speed level was treated with seven levels of angle of attack (α), namely, -15°, -5°, 0°, 10°, 15°, 20°, and 25°. Each α level was treated with six levels of change in the aircraft elevator deflection angle (δ): -15°, 0°, 10°, 20°, 30°, and 45°. The results showed that the maximum values of CD and CL were obtained at δ = 45°, whereas the maximum value of CL/CD was obtained at δ = 45°.